Economic evaluation of productive and reproductive indicators in dairy cows with different ages at first calving, in grazing systems - Fernández, R.; Biga, P.; Di Masso, R. J.; Marini, P. R. (Cuban Journal of Agricultural Science, 2020)
In livestock activity, profitability can be evaluated by calculating zootechnical indices, because of their relation with production and, consequently, to the main income source for the farmer. The aim of this study was to evaluate the importance of a group of productive-reproductive indicators, not always valued, in the economic results of milk production in system based on grazing. Retrospective data was used, corresponding to lactations of 1,785 primiparous Holstein cows, American-Canadian biotype, collected between 1999-2016 in two establishments located in Entre Ríos province, Argentina. Fifty members from each of the following three age groups at first calving were randomly chosen: Group 1: 750 days (24 months), Group 2: 840 days (27 months) and Group 3: 1,098 days (32 months). Group characterization was based on values of the following indicators: total productive life, total milk production, milk index, productive days, number of calvings, production per lactation and mean calving interval. Significant differences between groups (p<0.05) were only observed for total productive life. Although all three groups produced similar amounts of milk, cows in the late calving age group resulted in higher incomes. It is concluded that indicators calving interval, efficiency in rearing, age at first calving and longevity, all of which are easy to register, acquire relevance when evaluating their impact while modeling the final economic result of the establishment, thus enabling the technical and managerial decision making, aimed to improve system profitability. Key Words: dairy cows, age at first calving, calving interval, longevity